Membangun Kepuasan Kerja Dosen: Sinergi antara Gaya Kepemimpinan dan Strategi Kompensasi - Wahyudi, Wahyudi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Lecturers' job satisfaction plays a critical role in enhancing the quality of higher education. Satisfied lecturers are more likely to demonstrate higher performance, greater institutional commitment, and active engagement in teaching and research. In light of the growing challenges faced by academic institutions, understanding the key drivers of job satisfaction has become increasingly important. This study investigates the influence of leadership and compensation on lecturers' job satisfaction using a quantitative approach. Data were gathered through a survey conducted among lecturers at a university, and analyzed using multiple linear regression to assess the relationship between the variables. The findings reveal that both leadership and compensation have a positive and significant impact on job satisfaction. With a determination coefficient (R²) of 0.755, the model explains 75.5% of the variance in job satisfaction, highlighting the strong influence of these two factors. Effective leadership—characterized by open communication, support, and professional development opportunities—significantly enhances satisfaction levels. Additionally, a fair and transparent compensation system contributes to improved motivation and retention. These results suggest that higher education institutions must invest in developing strong leadership practices and implementing competitive compensation strategies. By fostering a supportive work environment, universities can increase lecturer satisfaction and ultimately improve the quality of education.